2017
DOI: 10.1021/acs.macromol.7b02030
|View full text |Cite
|
Sign up to set email alerts
|

Primary Alkylphosphine–Borane Polymers: Synthesis, Low Glass Transition Temperature, and a Predictive Capability Thereof

Abstract: With a multitude of potential applications, poly­(phosphine–borane)­s are an interesting class of polymer comprising main-group elements within the inorganic polymer backbone. A new family of primary alkylphosphine–borane polymers was synthesized by a solvent-free rhodium-catalyzed dehydrocoupling reaction and characterized by conventional chemicophysical techniques. The thermal stability of the polymers is strongly affected by the size and shape of the alkyl side chain with longer substituents imparting great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…[2][3][4] Although their synthesis, via the catalytic dehydrogenation-polymerisation of phosphine-borane complexes, was first achieved some 20 years ago, catalysts remain almost exclusively based on iron, ruthenium, rhodium or iridium. [2][3][4][5][6][7][8][9][10][11] A metal-free stoichiometric approach was described by Manners, Scheer, and co-workers, who demonstrated the metal-free head-to-tail polymerisation of tert-butylphosphinoborane, which was generated in situ from the trimethylamine-stabilised monomer (Scheme 1a). 12 More recently, Manners and co-workers have reported that treatment with stoichiometric quantities of cyclic alkyl amino carbenes (CAACs) induces the dehydrogenative coupling of phosphine-boranes to provide access to primary-and, previously unprecedented, secondary polyphosphinoboranes (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Although their synthesis, via the catalytic dehydrogenation-polymerisation of phosphine-borane complexes, was first achieved some 20 years ago, catalysts remain almost exclusively based on iron, ruthenium, rhodium or iridium. [2][3][4][5][6][7][8][9][10][11] A metal-free stoichiometric approach was described by Manners, Scheer, and co-workers, who demonstrated the metal-free head-to-tail polymerisation of tert-butylphosphinoborane, which was generated in situ from the trimethylamine-stabilised monomer (Scheme 1a). 12 More recently, Manners and co-workers have reported that treatment with stoichiometric quantities of cyclic alkyl amino carbenes (CAACs) induces the dehydrogenative coupling of phosphine-boranes to provide access to primary-and, previously unprecedented, secondary polyphosphinoboranes (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…However, attempts to dehydrocouple phosphine-borane adducts under thermal conditions yielded either low molecular weight or poorly soluble materials, which lacked convincing structural characterisation by modern standards 2 , 24 , 25 . Since 1999 a rhodium-catalysed dehydrocoupling approach to prepare soluble, high-molecular-weight (P-monosubstituted)polyphosphinoboranes has been available 26 28 . Examples of iron and iridium-catalysed dehydrocouplings have also been reported as routes to high-molecular-weight poly(arylphosphinoboranes) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, much less is known about poly­(alkylphosphinoboranes). The synthesis of P -alkyl-substituted polymers would be expected to be significantly more challenging through catalytic dehydrocoupling routes because of the lower acidity of the P–H bond in the precursor due to the inductive effect of the alkyl group attached to phosphorus. , Consistent with this, dehydropolymerization of i BuPH 2 ·BH 3 gave a moderate molar mass polymer ( M w = 10,000–20,000 g mol –1 ) [ i BuPH–BH 2 ] n under forcing conditions (melt, 120 °C, 13 h) using [Rh­(μ-Cl)­(1,5-COD)] 2 (COD = cyclooctadiene) as a precatalyst (Scheme A) . More recent studies of the dehydropolymerization of alkyl phosphine–boranes using the same Rh precatalyst demonstrated that the dehydrocoupling of RPH 2 ·BH 3 (R = FcCH 2 , n Bu, n Hex, (2-Et)­Hex), in general, has given lower molar mass ( M n < 10,000 g mol –1 ) , and relatively branched materials with varied polydispersity index values ( D̵ = 1.2–5.0) under forcing thermal conditions (90–130 °C) and in the melt.…”
Section: Introductionmentioning
confidence: 95%